Effect of the addition of high‐temperature water on the properties of batter and bread made from gluten‐free rice flour. Issue 2 (17th January 2022) - Saito, Kumiko; Okouchi, Maya; Yamaguchi, Mana; Takechi, Tayori; Hatanaka, Yoshiro; Kitsuda, Koji; Mannari, Takayo; Takamura, Hitoshi
Abstract : Abstract: Increasing number of individuals worldwide are consuming gluten‐free products, for example, bread, for health and other reasons. However, gluten‐free products are currently expensive and/or their preparation involves the use of specialist machinery or food additives. In this study, we focused on the thickening effect of starch gelatinization and attempted to develop a novel method for gluten‐free rice flour bread production without the use of additives. We aimed to determine the effect of adding high‐temperature water to gluten‐free rice flour on the properties of the resulting batter, primarily gelatinization. The water was tested at temperatures between 50 and 80°C, in 2°C increments. For comparison, control bread from gluten‐free rice flour was made using cold (5°C) water. The addition of water at a temperature between 66 and 70°C significantly improved the specific volume and firmness of bread ( p  < 0.05, Dunnett's test; compared with control). Additionally, maintaining the gelatinization temperature of the bread batter for approximately 1–10 s and the degree of gelatinization of batter, approximately 5%–10%, were crucial for obtaining good‐quality bread. Further, the addition of water at a temperature above 78°C adversely affected the bread‐making properties. This simple method developed for making high‐quality bread from gluten‐free rice flour will make gluten‐free bread products more widely available to and acceptable by the consumers. Practical Application: Currently, making high‐quality bread from gluten‐free rice flour involves the use of food additives or special rice flour. Here, we present a simple method for producing high‐quality bread by manipulating the temperature of water added during the preparation of rice flour batter. We optimized the method by analyzing the gelatinization properties of the batter and determined the optimal water temperature suitable for bread making. This method yields high‐quality gluten‐free bread and is cost‐effective and simple to implement.